2017
DOI: 10.1371/journal.pone.0174172
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of 5-HT/AKH and octopamine on the crop contractions in adult Drosophila melanogaster: Evidence of a double brain-gut serotonergic circuitry

Abstract: This study showed that in adult Drosophila melanogaster, the type of sugar—either present within the crop lumen or in the bathing solution of the crop—had no effect on crop muscle contraction. What is important, however, is the volume within the crop lumen. Electrophysiological recordings demonstrated that exogenous applications of serotonin on crop muscles increases both the amplitude and the frequency of crop contraction rate, while adipokinetic hormone mainly enhances the crop contraction frequency. Convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 90 publications
2
22
2
Order By: Relevance
“…The present study demonstrated that the crop of adult female A. aegypti spontaneously contracts in vitro at a rate of ~6 contractions per min; which is noticeably lower than corresponding rates (15–90 contractions per min) in P. regina , M. domestica, and D. melanogaster (Haselton et al 2006; Kaminski et al 2002; Liscia et al 2012; Solari et al 2017, 2013; Stoffolano et al 2014b; Stoffolano et al 2013). Whether the lower spontaneous contraction rate in female mosquitoes is adaptive to their hematophagous life style remains to be determined.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…The present study demonstrated that the crop of adult female A. aegypti spontaneously contracts in vitro at a rate of ~6 contractions per min; which is noticeably lower than corresponding rates (15–90 contractions per min) in P. regina , M. domestica, and D. melanogaster (Haselton et al 2006; Kaminski et al 2002; Liscia et al 2012; Solari et al 2017, 2013; Stoffolano et al 2014b; Stoffolano et al 2013). Whether the lower spontaneous contraction rate in female mosquitoes is adaptive to their hematophagous life style remains to be determined.…”
Section: Discussioncontrasting
confidence: 59%
“…Similarly, 5-HT stimulates crop contractions in P. reginia and D. melanogaster (Liscia et al 2012; Solari et al 2017). The effects of 5-HT on the isolated mosquito crop in vitro suggest that in vivo the contractile activity of the crop can potentially be regulated by changes in hemolymph 5-HT levels and/or the release of 5-HT from 5-HT-immunoreactive neurons that innervate the crop of A. aegypti (Moffett and Moffett, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations